Book Reviews (Rev. Anal. Numér. Théor. Approx., 2000)
Book reviews for:Bernard Dacorogna and Paolo Marcellini, Implicit Partial Differential Equations, Progress in Nonlinear Partial Differential Equations and their Applications, Birkhauser Verlag, Basel-Boston-Berlin, 1999, XII+273 pp., ISBN 3-8176-4121-1 and 3-7643-4121-1. Reviewed by S. Cobzas.Analysis of Divergence - Control and Management of Divergent Processes, William O. Bray and Caslav V. Stanojevic (Editors),  Applied and Numerical Harmonic Analysis, Birkhauser Verlag, Boston-Basel-Berlin, 1999, XX+567 pp., ISBN 3-7643-4058-4 and 0-8176-4059-4. Reviewed by D. Trif.Flucher, Martin, Variational Problems with Concentration, Progress in Nonlinear Differential Equations and Their Applications; Vol. 36, Birkhauser, Basel-Boston-Berlin, 1999, VIII+163 pp., ISBN 3-7643-6136-0 and 0-8176-6136-0. Reviewed by R. Precup.Phillip I. Good, Resampling Methods. A Practical Guide to Data Analysis,  Birkhauser, Boston-Basel-Berlin, 1999, XXII+269 pp., ISBN 0-8176-4091-6 and 3-7643-4097-6. Reviewed by P. Blaga.George Gratzer, First steps in LATEX, Birkhauser Verlag Boston and Springer-Verlag New York, 1999, XX+131 pp., ISBN 0-8176-4132-7, 3-7643-4132-7. Reviewed by S. Cobzas.J. Stroeker, J. F. Kaashoek, Discovering Mathematics with Maple, An Interactive Exploration for Mathematicians, Engineers and Econometricians, Birkhauser, Boston-Basel-Berlin, 1999, XVII+227 pp., Paperback, ISBN 0-8176-6091-7 and 0-7643-6091-7. Reviewed by P. Blaga.